First, subtract color(red)(10) from each side of the equation to put the equation in standard quadratic for while keeping the equation balanced:
3x^2 + 13x - color(red)(10) = 10 - color(red)(10)
3x^2 + 13x - 10 = 0
We can now use the quadratic equation to solve this problem:
The quadratic formula states:
For color(red)(a)x^2 + color(blue)(b)x + color(green)(c) = 0, the values of x which are the solutions to the equation are given by:
x = (-color(blue)(b) +- sqrt(color(blue)(b)^2 - (4color(red)(a)color(green)(c))))/(2 * color(red)(a))
Substituting:
color(red)(3) for color(red)(a)
color(blue)(13) for color(blue)(b)
color(green)(-10) for color(green)(c) gives:
x = (-color(blue)(13) +- sqrt(color(blue)(13)^2 - (4 * color(red)(3) * color(green)(-10))))/(2 * color(red)(3))
x = (-color(blue)(13) +- sqrt(169 - (12 * color(green)(-10))))/6
x = (-color(blue)(13) +- sqrt(169 - (-120)))/6
x = (-color(blue)(13) +- sqrt(169 + 120))/6
x = (-color(blue)(13) +- sqrt(289))/6
x = (-color(blue)(13) - 17)/6 and x = (-color(blue)(13) + 17)/6
x = -30/6 and x = 4/6
x = -5 and x = 2/3
The Solution Set Is: x = {-5, 2/3}